Crisis Management in a Social Context: Sustainable Crisis Management Strategies for Organizations - Bustomi, Thomas (Universitas Negeri Makassar, 2023)
This qualitative research explores crisis management in the context of Indonesia, focusing on the development of sustainable crisis management strategies for organizations. Against the backdrop of Indonesia's vulnerability to various social, economic, and environmental challenges, this study aims to investigate how organizations navigate crises effectively while considering the social dimension. Employing in-depth interviews, content analysis of relevant documents, and participant observations, the research delves into the experiences of organizations operating in Indonesia during times of crisis. The findings reveal that organizations adopt multifaceted crisis management strategies that not only address the immediate operational aspects but also take into account the socio-cultural context. These strategies involve proactive stakeholder engagement, cultural sensitivity, and community-based approaches to crisis resolution. Moreover, the research uncovers the critical role of leadership and communication in shaping these sustainable crisis management strategies. Ultimately, this study contributes to the broader understanding of crisis management in a social context, providing insights that can inform the development of more resilient and socially responsible crisis management practices for organizations operating in Indonesia and similar contexts.